Tribological Behavior of Glycerol/Water-Based Magnetorheological Fluids in PMMA Point Contacts - Rosa, Wagner O.; Vereda, Fernando; de Vicente, Juan (Frontiers in Materials, 2019)
The understanding of the tribological behavior of magnetorheological fluids is crucial for many applications, in particular for those related with high quality surface finishing. In this contribution, we describe a thorough experimental investigation on the tribological properties of magnetorheological (MR) fluids in poly(methyl methacrylate) (PMMA) point contacts. First, magnetic iron oxide particles with diameters of approximately 0.4, 1,3 and 2.0 µm were prepared using wet chemistry procedures. Then, MR fluids were formulated by dispersion of the magnetic particles in glycerol/water mixtures. The tribological experiments were run in a PMMA ball-on-three plates tribometer and Stribeck regions were identified for a wide range of sliding speeds. The wear tracks were also visualized in a confocal microscope to correlate them with friction coefficient data. The results show the effect of both particle size and applied magnetic field in the friction coefficient and wear scar volume, suggesting a slight decrease on the wear process when the magnetic field is present.